Corrosive agent for 9Cr18 high-carbon martensitic stainless steel grain boundary and corrosion method thereof
By using a corrosive agent composed of 49-51 ml of nitric acid solution, 4.5-5.5 ml of hydrochloric acid solution and 14-16 ml of ethanol solution, the problem of difficult to clearly observe the grain boundaries of 9Cr18 high-carbon martensite stainless steel in the prior art is solved, and the effect of clear observation under an optical microscope is achieved. It is easy to operate, easy to obtain reagents, stable corrosion process, and good effect.
Patent Information
- Application Number
- CN202411834735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
It is difficult for the prior art to clearly observe the grain boundaries of 9Cr18 high-carbon martensitic stainless steel under an optical microscope, and common corrosive agents have problems such as inconvenient operation, rare reagents, unstable corrosion process, and poor corrosion effect.
The corrosion agent consisting of 49-51 ml of nitric acid solution, 4.5-5.5 ml of hydrochloric acid solution, and 14-16 ml of ethanol solution were used. After mixing them uniformly and letting them stand for 1 hour, the degreasing cotton was used to rub the corrosion on the surface of the sample until the detection surface changed from a bright state to a light gray color.
The grain boundaries of 9Cr18 high-carbon martensitic stainless steel can be clearly observed under an optical microscope. The operation is simple, the reagents are easy to obtain, the corrosion process is stable, and the corrosion effect is good.
Smart Images

Figure CN119663284A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thin films, in particular to an etchant for the grain boundary of 9Cr18 high-carbon martensitic stainless steel and a corrosion method thereof. Background Art
[0002] High carbon martensitic stainless steel has high hardness, strength, good corrosion resistance and wear resistance, and is widely used in bearing rings, bearing rolling elements, measuring tools, surgical instruments, knives and scissors, etc. The matrix of this type of stainless steel contains a high carbon element, and the metallographic structure after quenching is generally martensitic matrix + eutectic carbide + residual austenite + secondary carbide. The shape, size and distribution of carbides in high carbon martensitic stainless steel will have a great influence on the material properties, so it is necessary to observe and measure the grain boundaries and carbides of high carbon martensitic stainless steel.
[0003] However, due to the high carbon and chromium contents, carbides are easily generated. The secondary carbides that are not dissolved after quenching will be evenly distributed on the matrix and grain boundaries, resulting in the use of commonly used ferric chloride, hydrochloric acid and alcohol etching agents. It is difficult to control the corrosion time, and it is difficult to clearly show the original austenite grain boundaries after corrosion, and thus it is difficult to rate the grain size. If picric acid is used, picric acid is an explosive reagent, a strictly controlled reagent, and dangerous to use. It is currently not available for purchase on the market. If in the actual metallographic analysis and testing process, the grain size is rated by observing the quenched martensite structure returning to the original austenite, it will lead to obvious deviations in the rating results. Summary of the invention
[0004] Based on this, the purpose of the present invention is to provide an etchant for the grain boundaries of 9Cr18 high carbon martensitic stainless steel, which can clearly observe the grain boundaries of 9Cr18 high carbon martensitic stainless steel under an optical microscope, and has the advantages of convenient operation, easy availability of reagents, stable corrosion process and good corrosion effect.
[0005] The technical solution of the present invention is achieved by the following methods:
[0006] A 9Cr18 high-carbon martensitic stainless steel grain boundary corrosive agent comprises 49-51 ml of nitric acid solution, 4.5-5.5 ml of hydrochloric acid solution and 14-16 ml of ethanol solution.
[0007] The etchant for the grain boundary of 9Cr18 high carbon martensitic stainless steel of the present invention can clearly observe the grain boundary of 9Cr18 high carbon martensitic stainless steel under an optical microscope, and the reagent is easily available, and has the advantages of convenient operation, easy availability of reagents, stable corrosion process and good corrosion effect.
[0008] Further, it includes 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution.
[0009] Furthermore, the concentration of the nitric acid solution is 65%-68%, the concentration of the hydrochloric acid solution is 36%-38%, and the concentration of the ethanol solution is 95%.
[0010] The present invention also provides a method for corroding the grain boundary of 9Cr18 high carbon martensitic stainless steel as described above, comprising the following steps:
[0011] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the ratio, and let it stand for 1 hour to obtain the corrosive agent;
[0012] Sample treatment: 9Cr18 high carbon martensitic stainless steel was ground and polished until there were no scratches on the surface, then rinsed with clean water and dried to obtain the sample;
[0013] Sample corrosion: rub the absorbent cotton that has fully absorbed the corrosive agent on the sample surface until the test surface changes from a bright state to a light gray, and then the corroded sample is obtained. The corroded sample is rinsed with clean water and blown dry. A corrosion method for 9Cr18 high carbon martensitic stainless steel is provided, which can clearly observe the grain boundary of 9Cr18 high carbon martensitic stainless steel under an optical microscope, and the operation is simple and time-saving.
[0014] Furthermore, the method further comprises the following steps: the corroded sample is rinsed with clean water and blown dry, and then observed and photographed with an optical microscope to obtain a metallographic picture.
[0015] Furthermore, in the sample corrosion step, the corrosion temperature is 25°C.
[0016] Furthermore, in the sample corrosion step, the corrosion time is 5 to 15 seconds. If the corrosion time is less than 5 seconds, the grain boundary corrosion is not clear, and if the corrosion time is greater than 15 seconds, the intragranular structure is revealed.
[0017] Furthermore, in the etching agent preparation step, the standing temperature is 25°C.
[0018] Furthermore, the processing states of the 9Cr18 high carbon martensitic stainless steel include hot rolled state, quenched state and tempered state after quenching.
[0019] Furthermore, the chemical element content (weight percentage) of the 9Cr18 high carbon martensitic stainless steel is: 0.90% to 1.00% C, 17.00% to 19.00% Cr, Mn≤0.80%, Si≤0.80%, Ni≤0.25%, Cu≤0.25%, S≤0.020%, P≤0.035% and the balance Fe.
[0020] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a 500-fold metallographic phase diagram of the 9Cr18 high carbon martensitic stainless steel of Example 1 of the present invention;
[0022] Figure 2 This is a 1000-fold metallographic phase diagram of the 9Cr18 high carbon martensitic stainless steel of Example 1 of the present invention;
[0023] Figure 3 This is a 500-fold metallographic diagram of the 9Cr18 high-carbon martensitic stainless steel of Example 2 of the present invention;
[0024] Figure 4 This is a 1000-fold metallographic phase diagram of 9Cr18 high carbon martensitic stainless steel according to Example 2 of the present invention;
[0025] Figure 5 This is a 500-fold metallographic diagram of the 9Cr18 high carbon martensitic stainless steel of Comparative Example 1 of the present invention;
[0026] Figure 6 This is a 1000-fold metallographic diagram of the 9Cr18 high carbon martensitic stainless steel of Comparative Example 1 of the present invention;
[0027] Figure 7 This is a 500-fold metallographic diagram of the 9Cr18 high carbon martensitic stainless steel of Comparative Example 2 of the present invention;
[0028] Figure 8 This is a 1000-fold metallographic diagram of the 9Cr18 high carbon martensitic stainless steel of Comparative Example 2 of the present invention;
[0029] Fig. 9 This is a 500-fold metallographic diagram of the 9Cr18 high carbon martensitic stainless steel of Comparative Example 3 of the present invention;
[0030] Fig.10 This is a 1000-fold metallographic phase diagram of the 9Cr18 high carbon martensitic stainless steel of Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0031] It should be clear that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the embodiments of the present application.
[0032] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0033] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims. In the description of the present application, it should be understood that the terms "first", "second", "third", etc. are only used to distinguish similar objects, and do not have to be used to describe a specific order or sequence, nor can they be understood as indicating or implying relative importance. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.
[0034] In addition, in the description of this application, unless otherwise specified, "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0035] It should be understood that the embodiments of the present application are not limited to the precise structures described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof. The scope of the embodiments of the present application is limited only by the appended claims.
[0036] The present invention provides an etchant for corroding 9Cr18 high carbon martensitic stainless steel, comprising 49-51 ml of nitric acid solution, 4.5-5.5 ml of hydrochloric acid solution and 14-16 ml of ethanol solution. The grain boundary of 9Cr18 high carbon martensitic stainless steel can be clearly observed under an optical microscope, and the etchant has the advantages of convenient operation and easy availability of reagents.
[0037] Further, the corrosive agent used for corroding 9Cr18 high carbon martensitic stainless steel includes 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution.
[0038] Further, the concentration of the nitric acid solution is 65%-68%, the concentration of the hydrochloric acid solution is 36%-38%, and the concentration of the ethanol solution is 95%. The concentrations of the nitric acid solution, the hydrochloric acid solution, and the ethanol solution described in this application are all mass concentrations.
[0039] The present invention also provides a method for corroding the grain boundary of 9Cr18 high carbon martensitic stainless steel as described above, comprising the following steps:
[0040] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the ratio, and let it stand for 1 hour to obtain the corrosive agent;
[0041] Sample treatment: 9Cr18 high carbon martensitic stainless steel was ground and polished until there were no scratches on the surface, then rinsed with clean water and dried to obtain the sample;
[0042] Sample corrosion: rub the absorbent cotton that has fully absorbed the corrosive agent on the sample surface until the test surface changes from a bright state to a light gray, and then the corroded sample is obtained. The corroded sample is rinsed with clean water and blown dry. A corrosion method for 9Cr18 high carbon martensitic stainless steel is provided, which can clearly observe the grain boundary of 9Cr18 high carbon martensitic stainless steel under an optical microscope, and the operation is simple and time-saving.
[0043] Furthermore, the method further comprises the following steps: the corroded sample is rinsed with clean water and blown dry, and then observed and photographed with an optical microscope to obtain a metallographic picture.
[0044] Furthermore, in the sample corrosion step, the corrosion temperature is 25°C.
[0045] Furthermore, in the sample corrosion step, the corrosion time is 5 to 15 seconds.
[0046] Furthermore, in the etching agent preparation step, the standing temperature is 25°C.
[0047] Furthermore, the processing states of the 9Cr18 high carbon martensitic stainless steel include hot rolled state, quenched state and tempered state after quenching.
[0048] Furthermore, the chemical element content (weight percentage) of the 9Cr18 high carbon martensitic stainless steel is: 0.90% to 1.00% C, 17.00% to 19.00% Cr, Mn≤0.80%, Si≤0.80%, Ni≤0.25%, Cu≤0.25%, S≤0.020%, P≤0.035% and the balance Fe.
[0049] It should be noted that the 9Cr18 high carbon martensitic stainless steel material used in the embodiment of the present invention has the following main chemical element contents (by weight): C content 0.90% to 1.00%, Mn content ≤0.80%, Si content ≤0.80%, Cr content 17.00% to 19.00%, Ni content ≤0.25%, Cu content ≤0.25%, S content ≤0.020%, P content ≤0.035%, and the balance is Fe.
[0050] Example 1
[0051] This embodiment provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution, wherein the concentration of the nitric acid solution is 65%, the concentration of the hydrochloric acid solution is 36%, and the concentration of the ethanol solution is 95%.
[0052] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this embodiment comprises the following steps:
[0053] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0054] Sample processing: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there are no scratches on the surface, rinse it with clean water and blow it dry to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this embodiment is hot rolling at 1050°C and then air cooling, and the grains have a certain metal flow direction.
[0055] Sample corrosion: Dip the absorbent cotton into the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample. The rubbing time is 10s, the rubbing temperature is 25℃, and the test surface changes from a bright state to a light gray state to obtain the corroded sample. Rinse the corroded sample with clean water and blow dry. Observe the metallographic structure of the corroded sample with a metallographic optical microscope and take pictures to obtain a 500x metallographic picture Figure 1 And 1000 times metallographic pictures Figure 2 . The grain boundaries are clear.
[0056] Example 2
[0057] This embodiment provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0058] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this embodiment comprises the following steps:
[0059] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0060] Sample processing: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there are no scratches on the surface, rinse it with clean water and blow it dry to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this embodiment is to keep it at 1050°C for 40 minutes, then oil quench it, and the grains are recrystallized.
[0061] Sample corrosion: Dip the absorbent cotton into the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample. The rubbing time is 10s, the rubbing temperature is 25℃, and the test surface changes from a bright state to a light gray state to obtain the corroded sample. Rinse the corroded sample with clean water and blow dry. Observe the metallographic structure of the corroded sample with a metallographic optical microscope and take pictures to obtain a 500x metallographic picture Figure 3 And 1000 times metallographic pictures Figure 4 . The grain boundaries are clear.
[0062] Comparative Example 1
[0063] This comparative example provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0064] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this comparative example comprises the following steps:
[0065] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0066] Sample treatment: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there is no scratch on the surface, rinse it with clean water and blow dry it to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this comparative example is oil quenching after keeping it at 1050°C for 40 minutes.
[0067] Sample corrosion: Immerse the absorbent cotton in the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample. The rubbing time is 3s, the rubbing temperature is 25℃, and the test surface changes from a bright state to a light gray state to obtain the corroded sample. Rinse the corroded sample with clean water and blow dry. Use a metallographic optical microscope to observe and photograph the metallographic structure of the corroded sample to obtain a 500x metallographic picture Figure 5 And 1000 times metallographic pictures Figure 6 The etching time is not enough and the grain boundaries are not clear enough.
[0068] Comparative Example 2
[0069] This comparative example provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0070] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this comparative example comprises the following steps:
[0071] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0072] Sample treatment: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there is no scratch on the surface, rinse it with clean water and blow dry it to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this comparative example is oil quenching after keeping it at 1050°C for 40 minutes.
[0073] Sample corrosion: Dip the absorbent cotton into the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample. The rubbing time is 18s, the rubbing temperature is 25℃, and the test surface changes from a bright state to a light gray state to obtain the corroded sample. Rinse the corroded sample with clean water and blow dry. Observe the metallographic structure of the corroded sample with a metallographic optical microscope and take pictures to obtain a 500x metallographic picture Figure 7 And 1000 times metallographic pictures Figure 8 . If the corrosion time is too long, the intracrystalline structure will be revealed.
[0074] Comparative Example 3
[0075] This comparative example provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 50 ml of nitric acid solution, 10 ml of hydrochloric acid solution and 15 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0076] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this comparative example comprises the following steps:
[0077] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0078] Sample processing: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there is no scratch on the surface, rinse it with clean water and blow dry it to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this comparative example is oil quenching after keeping at 1050°C for 40 minutes, and the grains are recrystallized.
[0079] Sample corrosion: Dip the absorbent cotton into the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample. The rubbing time is 10s, the rubbing temperature is 25℃, and the test surface changes from a bright state to a light gray state to obtain the corroded sample. Rinse the corroded sample with clean water and blow dry. Observe the metallographic structure of the corroded sample with a metallographic optical microscope and take pictures to obtain a 500x metallographic picture Fig. 9 And 1000 times metallographic pictures Fig.10 In this comparative example, the amount of hydrochloric acid used was too much, the grain boundaries were not clearly shown, and the corrosion was intermittent. The intracrystalline structure was corroded, which also resulted in unclear grain boundaries and was not conducive to grain size measurement.
[0080] Comparative Example 4
[0081] This comparative example provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 60 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0082] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this comparative example comprises the following steps:
[0083] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0084] Sample processing: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there is no scratch on the surface, rinse it with clean water and blow dry it to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this comparative example is oil quenching after keeping at 1050°C for 40 minutes, and the grains are recrystallized.
[0085] Sample corrosion: soak the absorbent cotton in the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample, wherein the rubbing time is 10s, the rubbing temperature is 25°C, the detection surface changes from a bright state to a light gray, and the corroded sample is obtained, the corroded sample is rinsed with clean water and blown dry, and the metallographic structure of the corroded sample is observed with a metallographic optical microscope. In this comparative example, the amount of nitric acid used is too much, the grain boundary is not clearly shown, it is intermittent, and the intracrystalline structure is corroded, which also leads to unclear grain boundaries, which is not conducive to grain size measurement.
[0086] Comparative Example 5
[0087] This comparative example provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 40 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0088] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this comparative example comprises the following steps:
[0089] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0090] Sample processing: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there is no scratch on the surface, rinse it with clean water and blow dry it to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this comparative example is oil quenching after keeping at 1050°C for 40 minutes, and the grains are recrystallized.
[0091] Sample corrosion: soak the absorbent cotton in the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample, wherein the rubbing time is 10s, the rubbing temperature is 25℃, the detection surface changes from a bright state to a light gray, and the corroded sample is obtained, the corroded sample is rinsed with clean water and blown dry, and the metallographic structure of the corroded sample is observed with a metallographic optical microscope. In this comparative example, the amount of nitric acid used is too small, the grain boundary is not clearly shown, it is intermittent, and the intracrystalline structure is corroded, which also leads to unclear grain boundaries, which is not conducive to grain size measurement.
[0092] Comparative Example 6
[0093] This comparative example provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 25 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0094] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this comparative example comprises the following steps:
[0095] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0096] Sample processing: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there is no scratch on the surface, rinse it with clean water and blow dry it to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this comparative example is oil quenching after keeping at 1050°C for 40 minutes, and the grains are recrystallized.
[0097] Sample corrosion: soak the absorbent cotton in the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample, wherein the rubbing time is 10s, the rubbing temperature is 25℃, the detection surface changes from a bright state to a light gray, and the corroded sample is obtained, the corroded sample is rinsed with clean water and blown dry, and the metallographic structure of the corroded sample is observed with a metallographic optical microscope. In this comparative example, the amount of ethanol used is too much, the grain boundary is not clearly shown, it is intermittent, and the intracrystalline structure is corroded, which also leads to unclear grain boundaries, which is not conducive to grain size measurement.
[0098] Comparative Example 7
[0099] This comparative example provides a 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, including 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 10 ml of ethanol solution, wherein the concentration of the nitric acid solution is 68%, the concentration of the hydrochloric acid solution is 38%, and the concentration of the ethanol solution is 95%.
[0100] The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel of this comparative example comprises the following steps:
[0101] Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the proportion, seal and stand at 25°C for 1 hour to obtain the corrosive agent;
[0102] Sample processing: After grinding and polishing the 9Cr18 high carbon martensitic stainless steel until there is no scratch on the surface, rinse it with clean water and blow dry it to obtain a sample; wherein, the material process state of the 9Cr18 high carbon martensitic stainless steel material used in this comparative example is oil quenching after keeping at 1050°C for 40 minutes, and the grains are recrystallized.
[0103] Sample corrosion: soak the absorbent cotton in the corrosive agent to fully absorb the corrosive agent, use tweezers to hold the absorbent cotton that has fully absorbed the corrosive agent and rub it on the surface of the sample, wherein the rubbing time is 10s, the rubbing temperature is 25℃, the detection surface changes from a bright state to a light gray, and the corroded sample is obtained, the corroded sample is rinsed with clean water and blown dry, and the metallographic structure of the corroded sample is observed with a metallographic optical microscope. In this comparative example, the amount of ethanol used is too small, the grain boundary is not clearly shown, it is intermittent, and the intracrystalline structure is corroded, which also leads to unclear grain boundaries, which is not conducive to grain size measurement.
[0104] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent, characterized in that: It includes 49-51 ml of nitric acid solution, 4.5-5.5 ml of hydrochloric acid solution and 14-16 ml of ethanol solution.
2. The 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent according to claim 1, characterized in that: Includes 50 ml of nitric acid solution, 5 ml of hydrochloric acid solution and 15 ml of ethanol solution.
3. The 9Cr18 high carbon martensitic stainless steel grain boundary corrosive agent according to claim 1, characterized in that: The concentration of the nitric acid solution is 65%-68%, the concentration of the hydrochloric acid solution is 36%-38%, and the concentration of the ethanol solution is 95%.
4. A method for etching the grain boundaries of 9Cr18 high carbon martensitic stainless steel according to any one of claims 1 to 3, characterized in that: The following steps are involved: Preparation of the corrosive agent: uniformly mix the nitric acid solution, the hydrochloric acid solution and the ethanol solution according to the ratio, and let it stand for 1 hour to obtain the corrosive agent; Sample treatment: 9Cr18 high carbon martensitic stainless steel was ground and polished until there were no scratches on the surface, then rinsed with clean water and dried to obtain the sample; Sample corrosion: Rub the absorbent cotton that has fully absorbed the corrosive agent on the surface of the sample until the test surface changes from a bright state to a light gray to obtain the corroded sample. Rinse the corroded sample with clean water and blow dry.
5. The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel according to claim 1, characterized in that: The following steps are also included: The corroded sample was rinsed with clean water and dried, and then observed and photographed with an optical microscope to obtain a metallographic picture.
6. The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel according to claim 1, characterized in that: In the sample etching step, the temperature of the abrasion was 25°C.
7. The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel according to claim 1, characterized in that: In the sample corrosion step, the corrosion time is 5 to 15 seconds.
8. The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel according to claim 1, characterized in that: In the etching agent preparation step, the standing temperature is 25°C.
9. The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel according to claim 1, characterized in that: The process states of the 9Cr18 high carbon martensitic stainless steel include hot rolled state, quenched state and tempered state after quenching.
10. The method for etching the grain boundary of 9Cr18 high carbon martensitic stainless steel according to claim 1, characterized in that: The chemical element contents (by weight) of the 9Cr18 high carbon martensitic stainless steel are: 0.90% to 1.00% C, 17.00% to 19.00% Cr, Mn≤0.80%, Si≤0.80%, Ni≤0.25%, Cu≤0.25%, S≤0.020%, P≤0.035% and the balance Fe.
Citation Information
Cited By
Corrosion method of high-manganese austenite low-temperature steel metallographic specimen for LNG (Liquefied Natural Gas) storage tank
CN120489697A